Implementasi Minimum Quantity Lubrication (MQL) Pada Pembuatan Ulir Luar Material Magnesium - Arinal Hamni; Aditya Pratama; Gusri Akhyar Ibrahim (Manutech : Jurnal Teknologi Manufaktur, 2022)
Development of technology, has been to use of metal as the main material in industrial manufacture. In the machining, material of magnesium has excellent and beneficial characteristics, but it also has some disadvantages, one of them is very flammable because it has a low flash point. High generated temperatures can cause tool wear and contribute to thread accuuracy. Geometry errors in threading when cutting by lathe machine is influenced by diameter of cutting tool, depth of cut, and spindle speed. This study aims to analyze errors of response such as pitch errors, high thread errors, and thread angle errors. The machining trials of magnesium alloy AZ31 used by using Minimum Quantity Lubrication (MQL) method with lubricant of coconut oil. Diameter of threaded of 10, and 14 mm, depth of cut of 0.46 0.23, 0.3067, mm and a spindle speed of 424, 212, 424 rpm. The result shows that the Minimum Quantity Lubrication (MQL) technique with a diameter of 10 mm, a depth of cut of 0.46 mm and spindle speed of 424 rpm generated the best condition, in which pitch error of 0.012 mm and height thread error of 0.011533 mm.  Meanwhile the best result for thread angle error of 0.3866° in which reached at diameter of 10 mm, spindle speed of 212 rpm, and a depth of cut of 0.23 mm. Lubrication with implementing MQL technique has given real contribution to reduce the errors or increase the threaded precision.